Determination of alkylamines in atmospheric aerosol particles: a comparison of gas chromatography–mass spectrometry and ion chromatography approaches - R.-J. Huang (Atmospheric Measurement Techniques, 2014)
In recent years low molecular weight alkylamines have been recognized to play an important role in particle formation and growth in the lower atmosphere. However, major uncertainties are associated with their atmospheric processes, sources and sinks, mostly due to the lack of ambient measurements and the difficulties in accurate quantification of alkylamines at trace level. In this study, we present the evaluation and optimization of two analytical approaches, i.e., gas chromatography–mass spectrometry (GC-MS) and ion chromatography (IC), for the determination of alkylamines in aerosol particles. Alkylamines were converted to carbamates through derivatization with isobutyl chloroformate for GC-MS determination. A set of parameters affecting the analytical performances of the GC-MS approach, including reagent amount, reaction time and pH value, was evaluated and optimized. The accuracy is 84.3–99.1%, and the limits of detection obtained are 1.8–3.9 pg (or 0.02–0.04 ng m−3). For the IC approach, a solid-phase extraction (SPE) column was used to separate alkylamines from interfering cations before IC analysis. 1–2% (v/v) of acetone (or 2–4% (v/v) of acetonitrile) was added to the eluent to improve the separation of alkylamines on the IC column. The limits of detection obtained are 2.1–15.9 ng (or 0.9–6.4 ng m−3), and the accuracy is 55.1-103.4%. The lower accuracy can be attributed to evaporation losses of amines during the sample concentration procedure. Measurements of ambient aerosol particle samples collected in Hong Kong show that the GC-MS approach is superior to the IC approach for the quantification of primary and secondary alkylamines due to its lower detection limits and higher accuracy.